Applications of diffusion tensor imaging integrated with neuronavigation to prevent visual damage during tumor resection in the optic radiation area - Shi, Jianwei; Lu, Dafeng; Pan, Ruihan; Chen, Hairong; Teng, Hong; Xu, Yang; Bo, Fuduo; Zhou, Qi; Zhang, Yansong (Frontiers in Oncology, 2022)
Background: Intracranial tumors involving the temporo-occipital lobe often compress or destroy the optic radiation (OpR), resulting in decreased visual function. The aim of this study is to explore the value of diffusion tensor imaging (DTI) tractography integrated with neuronavigation to prevent visual damage when resecting tumors involving the OpR and find potential factors affecting patients’ visual function and quality of life (QOL). Methods: Our study is a cross-sectional study that included 28 patients with intracranial tumors in close morphological relationship with the OpR recruited between January 2020 and February 2022. The surgical incision and approach were preoperatively designed and adjusted according to the DTI tractography results and visual function scores. All patients underwent examinations of visual acuity (VA) and visual field index (VFI) and completed visual function and QOL scales at admission and 2 months after discharge. Logistic regression and linear regression analysis were conducted to evaluate clinical factors potentially affecting pre/postoperative OpR morphology, VA, VFI, visual function, and QOL. Results: Lesion size was the main factor found to affect visual function (β = -0.74, 95%CI: -1.12~-0.36, P = 0.05), VA (left: β = -0.11, 95%CI: -0.14~-0.08, P < 0.001; right: β = -0.15, 95%CI: -0.17~-0.13, P < 0.001), and VFI (left: β = -0.11, 95%CI: -0.14~-0.08, P < 0.001; right: β = -0.14, 95%CI: -0.16~-0.12, P < 0.001). Lesion size, edema, and involvement of the lateral ventricle temporal horn were factors affecting OpR morphology and QOL. The 28 patients showed significantly improved VA, VFI, visual function, and QOL results (P < 0.05) 2 months after discharge. Conclusions: Combining DTI of OpR mapping and microscopic-based neuronavigation aided precise mapping and thus preservation of visual function in patients undergoing tumor resection. Potential clinical factors affecting patients’ visual function and QOL scores were identified which are useful for assessing a patient's condition and predicting prognosis.